2017
DOI: 10.1111/epi.13650
|View full text |Cite
|
Sign up to set email alerts
|

Use of the ketogenic diet in the neonatal intensive care unit—Safety and tolerability

Abstract: Drug-resistant epilepsy poses a challenge in neonatal patients, especially those in the neonatal intensive care unit (NICU), who have various secondary comorbidities. We present results of four children with a history of drug-resistant epilepsy for whom a ketogenic diet was initiated and used in the NICU. A nonfasting induction into ketosis over 1-2 weeks was utilized, with gradual increases in the ketogenic ratio every 2-3 days. Data were collected retrospectively from a database, which included medical histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 9 publications
5
45
0
2
Order By: Relevance
“…A recent case report illustrates that KDTs are safe and effective for infants as young as 6 weeks. 11 In fact, there is now preliminary evidence that children younger than age 2 years may be an ideal age population in which to start the KD. 12,13 Specific guidelines for prescribing KDTs to infants have been created in Europe.…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent case report illustrates that KDTs are safe and effective for infants as young as 6 weeks. 11 In fact, there is now preliminary evidence that children younger than age 2 years may be an ideal age population in which to start the KD. 12,13 Specific guidelines for prescribing KDTs to infants have been created in Europe.…”
Section: Patient Selectionmentioning
confidence: 99%
“…In addition, breastfeeding is possible by either calculating the amount of breastmilk into a 3:1 formula or potentially allowing it briefly on demand. 11,14 The KD may also be delivered as a blenderized formula created from pureed foods, although there are no published clinical trials regarding its use at this time. The blenderized formula should be prepared with a high-quality blender to prevent blockage of the feeding tube, with the addition of a liquid fat source, diluted with water, and supplemented with micronutrients.…”
Section: Specific Diet Selection and Provisionmentioning
confidence: 99%
“…In our search, we also uncovered several studies that examined a specific age range. For instance, three studies investigated KD in infants (zero-two years old) [27,32,33], and 13 studies included children between one and 18 years of age [21, 24, 28, 34-38, 41, 43, 46, 53, 54]. Additionally, our search retrieved four studies investigating cognitive improvements in adult patients with epilepsy [44,47,49,51].…”
Section: Cognitive Benefits Of Kd Are Found In Infants Children Andmentioning
confidence: 99%
“…Most patients are good responders, weaning off infusion and successfully reaching ketosis, but the number of AEDs did not change significantly before and after undertaking a KDT [40,43]. The age of patients has varied across studies, but even 6 to 10-week-old neonates with RE are reported to tolerate KDTs well [42,50]. Intravenous (IV) KDT is recommended for patients with underlying concomitant ileus [41,44,48], and early administration of IV KDT should be considered before switching to an enteral route [44].…”
Section: The Gut-brain Axis and Kdtsmentioning
confidence: 99%
“…Contrary to a conventional view, under 2 years of age may be the optimum time to initiate a KDT because of the metabolic advantages of infants [50][51][52][53][54][55]. Numerous studies provide evidence for the advantages of using KDTs in infants with RE.…”
Section: Use Of Kdts For Infants With Rementioning
confidence: 99%